2021
DOI: 10.7150/ijms.48134
|View full text |Cite
|
Sign up to set email alerts
|

A review of linc00673 as a novel lncRNA for tumor regulation

Abstract: Long non-coding RNAs (LncRNAs) act as regulators and play important roles in a variety of biological processes. These regulators constitute a huge information network among genes and participate in the pathophysiological process of human diseases. Increasing evidence has demonstrated that LncRNA, as an oncogene or tumor suppressor gene, is closely related to the occurrence and development of tumors. Linc00673 is a recently discovered LncRNA molecule that is dysregulated in several solid tumors. Moreover, its g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 73 publications
(113 reference statements)
0
7
0
Order By: Relevance
“…These results were similar to the previous meta-analysis by Cao et al They reported that linc00673 demonstrated significantly prognostic value 38 . Similarly, Zhu in his literature review article explored that the high expression of linc00673, which acts as a pro-oncogene, is related to adverse outcomes for patients 39 . Moreover, our results showed that in patients with malignancy, the increased expression of linc00673 was associated with later T stage and tumour stage and an increased likelihood of lymph node metastasis and distant metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…These results were similar to the previous meta-analysis by Cao et al They reported that linc00673 demonstrated significantly prognostic value 38 . Similarly, Zhu in his literature review article explored that the high expression of linc00673, which acts as a pro-oncogene, is related to adverse outcomes for patients 39 . Moreover, our results showed that in patients with malignancy, the increased expression of linc00673 was associated with later T stage and tumour stage and an increased likelihood of lymph node metastasis and distant metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…We selected rs11655237 because this SNP was reported to be correlated with the risks of different cancer types [ 42 ]. Moreover, two other SNPs (rs6501551 and rs9914618) located in LINC00673 were selected based on their functional potential with RegulomeDB scores of <3 obtained from the RegulomeDB database.…”
Section: Methodsmentioning
confidence: 99%
“…Authors have demonstrated that smokers are more susceptible to the risk of lymphatic spread, whereas, LINC00673 and rs9914618 single-nucleotide-polymorphism (SNP) are associated with tumour progression in the case of betel nut chewing or smoking in OSCC [ 130 ]. The higher expression of LINC00673 represents a positive correlation with tumour size, higher TNM staging, and also with recurrence, irrespective of risk factors in OSCC [ 131 ]. The upregulation of HIFCAR is seen in OSCC and it is correlated with advanced tumour staging and so, it acts as a prognostic biomarker.…”
Section: Functional Dysregulation Of Lncrnas In Oral Squamous Cell Ca...mentioning
confidence: 99%